KMTNet Time-series Photometry of the Doubly Eclipsing Binary Stars Located in the Large Magellanic Cloud. (2nd April 2018) - Hong, Kyeongsoo; Koo, Jae-Rim; Lee, Jae Woo; Kim, Seung-Lee; Lee, Chung-Uk; Park, Jang-Ho; Kim, Hyoun-Woo; Lee, Dong-Joo; Kim, Dong-Jin; Han, Cheongho
Abstract: We report the results of photometric observations for doubly eclipsing binaries OGLE-LMC-ECL-15674 and OGLE-LMC-ECL-22159, both of which are composed of two pairs (designated A&B) of a detached eclipsing binary located in the Large Magellanic Cloud. The light curves were obtained by high-cadence time-series photometry using the Korea Microlensing Telescope Network 1.6 m telescopes located at three southern sites (CTIO, SAAO, and SSO) between 2016 September and 2017 January. The orbital periods were determined to be 1.433 and 1.387 days for components A and B of OGLE-LMC-ECL-15674, respectively, and 2.988 and 3.408 days for OGLE-LMC-ECL-22159A and B, respectively. Our light curve solutions indicate that the significant changes in the eclipse depths of OGLE-LMC-ECL-15674A and B were caused by variations in their inclination angles. The eclipse timing diagrams of the A and B components of OGLE-LMC-ECL-15674 and OGLE-LMC-ECL-22159 were analyzed using 28, 44, 28, and 26 new times of minimum light, respectively. The apsidal motion period of OGLE-LMC-ECL-15674B was estimated by detailed analysis of eclipse timings for the first time. The detached eclipsing binary OGLE-LMC-ECL-15674B shows a fast apsidal period of 21.5 ± 0.1 years.